The Impacts of COVID-19 on Port Operations and Supply Chains: The Case of Sarawak Ports - Suresh Tiwari, Suman Tiwari; Khairuddin, Ashman Shahrudin; Badi, Isaac (International Journal of Supply Chain Management, 2024)
In the era of digitalisation, the disruptions, such as operational issues, posed by the outbreak of the coronavirus disease 2019 (COVID19) on port operations have been witnessed worldwide. To explore the current issue in detail, particularly the COVID-19 ramifications on port operations and supply chains, the current study aims to appraise key stakeholders' perspectives regarding specific COVID-19 impacts posed on the port operational processes within the areas of Kuching Port Authority, Miri Port Authority, and Rajang Port Authority in Sarawak. This study adopted the qualitative research methodology by conducting indepth interviews and the software Archive for Technology, Lifeworld, and Everyday Language text interpretation (ATLAS.ti) to systematically extract and analyse emerging data trends. This research revealed that Sarawak ports were significantly affected in terms of scheduling and resources, namely finance, manpower, equipment, and spare parts. This study contributed to the existing body of knowledge by highlighting the COVID-19 impacts on port operations and supply chains. The findings could be applicable in benchmarking and guiding future port management systems.